Reading the CEO's Face: The Effect of Facial Masculinity on the Readability of MD&A Reports - Yulianti Raharjo; Iman Harymawan; Yani Permatasari; Khairul Anuar Kamarudin (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: This study analyzes the relationship between CEO facial masculinity and the readability of management discussion and analysis reports (MDA). Furthermore, this study examines the interaction between CEO busyness and age in this relationship.Method: Cluster regression with fixed effects was used to examine 1,569 firm-years of non-financial firms listed on the Indonesia Stock Exchange from 2010-2019.Findings: The results show that firms led by masculine-faced CEOs proved to be statistically significant in increasing the readability of MDA reports, making it easier for them to read and understand. However, our findings also show that CEO busyness and age weaken the relationship between CEO facial masculinity and the readability of MDA reports. Novelty: This study is the first to examine the relationship between CEO facial masculinity and MDA readability. This study has implications for corporate management and regulators.